DNA methylation is differentially associated with environmental cadmium exposure based on sex and smoking status - Shama Virani (2018)
© 2015 The Authors. The adverse health effects of cadmium (Cd) are well known in human populations; however, much of what is known about biological mechanisms of Cd comes from in vitro and animal studies. The adverse health outcomes due to high levels of Cd exposure in the population of Mae Sot, Thailand have been extensively characterized. Here, for the first time, this population is being studied in an epigenetic context. The objective of this study was to characterize the association between DNA methylation markers and Cd exposure, taking into account sex and smoking differences, in an adult population at an increased risk of experiencing adverse health outcomes from high body burden of Cd. One hundred and sixty-nine residents from known exposure areas of Mae Sot, Thailand and one hundred residents from non-exposed areas nearby were surveyed in 2012. Urine and blood samples were collected for measurement of urinary Cd (UCd) and DNA methylation of Cd-related markers (DNMT3B, MGMT, LINE-1, MT2A). UCd levels were 7 times higher in the exposed compared to the unexposed populations (exposed median: 7.4 μg/L, unexposed median: 1.0 μg/L, p < 0.001). MGMT hypomethylation was associated with increasing levels of UCd in the total population. Sex-specific associations included MT2A and DNMT3B hypomethylation in women and LINE-1 hypermethylation in men with increasing UCd. Upon subanalysis, these associations separated by smoking status. In summary, environmental Cd exposure is associated with gene-specific DNA methylation in a sex and smoking dependent manner.